Pengaruh Digital Experience dan Customer Experience terhadap Loyalitas Penumpang Kereta Api Progo Rute Pasar Senen–Lempuyangan - Iqbal Nur Fazarun; Osly Usman; Ryna Parlyna (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the influence of digital experience and customer experience on passenger loyalty on the Progo Train route, Pasar Senen–Lempuyangan. The increasing digitalization of public transportation services through the Access by KAI application has highlighted the importance of examining the quality of digital experience and customer experience in maintaining passenger loyalty. The study employed a quantitative approach with a causal associative design. Data were collected from 150 respondents through a questionnaire with a five-point Likert scale using a purposive sampling technique. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software (Ringle et al., 2024). The results of the outer model evaluation showed that all indicators had outer loadings > 0.70, Average Variance Extracted (AVE) > 0.50, Composite Reliability (CR) and Cronbach's alpha > 0.70, thus all constructs were declared valid and reliable. The inner model test shows that digital experience has a positive and significant effect on passenger loyalty (β = 0.192; T = 2.237; p = 0.025). Customer experience also has a positive and significant effect on passenger loyalty (β = 0.243; T = 3.268; p = 0.001). The coefficient of determination (R²) of 0.133 indicates that both variables explain 13.3% of the variance in passenger loyalty. The customer experience variable has a more dominant influence than digital experience on Progo Train passenger loyalty.